Dual Role of Host Toll-Like Receptor 3 in Parasitic Diseases - Yixin Yang; Qilong Li; Yiwei Zhang; Ning Jiang; Qijun Chen (Frontiers in Bioscience-Landmark)
Parasitic diseases, caused by a diverse array of parasites, remain a substantial threat to global health. Toll-like receptor 3 (TLR3) represents a pivotal element in the innate immune system, distinguished by an ability to signal via the TIR-domain-containing adapter-inducing interferon-β (TRIF)-dependent pathway upon detecting pathogen-derived double-stranded RNA (dsRNA), exosomal RNA (exoRNA), and long non-coding RNA (lncRNA). Predominantly localized on endosomal membranes, TLR3 is extensively expressed in neurons, immune cells, fibroblasts, and epithelial cells. Upon activation, TLR3 engages adaptor molecules such as TRIF, facilitating the phosphorylation of TANK-binding kinase 1 and the subsequent activation of interferon regulatory factors. This signaling cascade triggers the production of type I interferons (IFN-α/β) and proinflammatory cytokines such as interleukin (IL)-6, IL-8, IL-12, and tumor necrosis factor-alpha, which are crucial for effective immune defense against infections. Recent findings highlight the essential role of TLR3 in parasitic infections by detecting nucleic acids from damaged cells to activate dendritic and natural killer cells. TLR3 also functions with other receptors, such as TLR2 and TLR4, to enhance cytokine production and improve parasite clearance. However, TLR3 overactivation can induce excessive, harmful inflammation and tissue damage, highlighting its dual role in balancing immune defense. This review comprehensively examines the TLR3 signaling pathway and its multifaceted role in various parasitic infections, including those caused by Plasmodium spp., Leishmania spp., Clonorchis sinensis, Schistosoma japonicum, Trichinella spiralis, and Neospora caninum.